Mathematic Problem Ability of Algebra Operation With Problem Based Learning Class VIII.1 SMP Bhayangkari Pekanbaru - Sinaga, Dwika Ananda Ayu Rahmawati (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
Mathematic problem solving ability is an important goal in mathematics learning. Problem solving involves a high-level thinking process, including visualization, association, abstraction, manipulation, reasoning, analysis, synthesis, and generalizations.This study aims to determine the mathematic problem solving abilityof students class VIII.1 SMP Bhayangkari such understanding problem, planning the problem solving, making the calculation, and checking the results. This study uses a problembased learning model, involving activity, collaborative, and centered on the students, so it will able to develop the ability independently. The test is an essay. Data was analyzed quantitatively to determine the level of ability. Thestages are: giving scores on item, writing total scores, then determining them. It is in a classical assesment, which is based on the classical quantitative analysis. The average score of the students is 91.30. This means that the mathematic problem solving ability of students is very good.